RuO(2) doped SnO(2) nanobipyramids on Si (100) as a field emitter - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Thin Solid Films, 2008)
Thin films of RuO(2): SnO(2) nanobipyramids have been grown on silicon (100) flat substrates, and their field emission behavior has been investigated. The field emission experiments have been performed in parallel plate configuration. In this experiment, the onset field for 0. 1 gA/ cm 2 current density has been found to be 0.2 V/mu m. The Fowler-Nordheim plot shows non-linear nature typical that of a semiconductor. The field enhancement factor has been estimated to be 35,600 cm(-1), indicating that the field emission originates from the nanometric features of the emitter. The current stability recorded at a preset value of I tA is observed to be good. Our field emission results on RuO(2): SnO(2) nanobipyramids indicate that, RuO(2): SnO(2) nanobipyramids are a potential candidate for futuristic field emission based devices. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emitter; field enhancement factor; ruthenium oxide; tin oxide